2019
DOI: 10.1128/aac.02612-18
|View full text |Cite
|
Sign up to set email alerts
|

Control of Klebsiella pneumoniae Infection in Mice by Using Dissolving Microarray Patches Containing Gentamicin

Abstract: Using a murine model of Klebsiella pneumoniae bacterial infection, we demonstrate that gentamicin dissolving microarray patches, applied to murine ears, could control K. pneumoniae infection. Mice treated with microarray patches had reduced bacterial burden in the nasal-associated lymphoid tissue and lungs compared with their untreated counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…IV antibiotic administration is not as convenient as oral therapy however, necessitating specially trained personnel and giving rise to issues such as needle-phobia and introduction of infection. More user-friendly parenteral delivery systems may have a role to play in this area, such as microneedle arrays, which have already demonstrated potential for this purpose. , …”
Section: Resultsmentioning
confidence: 99%
“…IV antibiotic administration is not as convenient as oral therapy however, necessitating specially trained personnel and giving rise to issues such as needle-phobia and introduction of infection. More user-friendly parenteral delivery systems may have a role to play in this area, such as microneedle arrays, which have already demonstrated potential for this purpose. , …”
Section: Resultsmentioning
confidence: 99%
“…Bacterial resistance problems have occurred in different parts of the body. Accordingly, several drug delivery systems have been discovered with various routes to deliver antimicrobial agents to overcome this resistance issue [ 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 ].…”
Section: Drug Delivery Approaches Via Different Routes To Overcome Antimicrobial Resistancementioning
confidence: 99%
“…In vitro transdermal delivery showed that microneedles were able to deliver around 4.45 mg of gentamicin after 6 h. In an in vivo study using rats, it was found that dissolving microneedles could deliver gentamicin transdermally at therapeutic levels. Furthermore, Rodgers et al evaluated the in vivo efficacy of gentamicin loaded dissolving microneedles in a murine model of K. pneumoniae bacterial infection [ 172 ]. The microneedles were applied to murine ears.…”
Section: Drug Delivery Approaches Via Different Routes To Overcome Antimicrobial Resistancementioning
confidence: 99%
“…As DMN are fabricated from water-soluble, biocompatible materials that dissolve in the skin post-insertion, they overcome the generation of biohazardous sharps wastes and any material that remains on the skin may be discarded in non-sharps waste 47. Thus, this circumvents the risk of injury and disease transmission from used or contaminated needles 4…”
Section: Circumventing Vaccine Delivery Challenges: Is the Solution Imentioning
confidence: 99%